Excel 2007 formulas - Walkenbach, John. (Mr Spreadsheet's bookshelf, 2007)
.Excel master John Walkenbach has shared his expertise into previuos editions of this bestseller. Now he shows you how to create finacial formulars, and more with excel 2007.